Fermentative hydrogen production from Jerusalem artichoke by Clostridium tyrobutyricum expressing exo-inulinase gene - Ling Jiang (Nature Portfolio, 2017)
Abstract Clostridium tyrobutyricum ATCC25755 has been reported as being able to produce significant quantities of hydrogen. In this study, the exo-inulinase encoding gene cloned from Paenibacillus polymyxa SC-2 was into the expression plasmid pSY6 and expressed in the cells of C. tyrobutyricum. The engineered C. tyrobutyricum strain efficiently fermented the inulin-type carbohydrates from Jerusalem artichoke, without any pretreatment being necessary for the production of hydrogen. A comparatively high hydrogen yield (3.7 mol/mol inulin-type sugar) was achieved after 96 h in a batch process with simultaneous saccharification and fermentation (SSF), with an overall volumetric productivity rate of 620 ± 60 mL/h/L when the initial total sugar concentration of the inulin extract was increased to 100 g/L. Synthesis of inulinase in the batch SSF culture was closely associated with strain growth until the end of the exponential phase, reaching a maximum activity of 28.4 ± 0.26 U/mL. The overall results show that the highly productive and abundant biomass crop Jerusalem artichoke can be a good substrate for hydrogen production, and that the application of batch SSF for its conversion has the potential to become a cost-effective process in the near future.